Flexural strengthening of pre-cracked RC slabs with prestressed NSM CFRP laminates and evaluation of strain loss - Hosseini, Mhoammadreza Mostakhdemin (2021)
The strengthening intervention of RC structures often involves already cracked concrete. To evaluate the effect of the level of damage prior to the strengthening (pre-cracks) on the behavior of the flexurally strengthened RC slabs with prestressed NSM CFRP laminates, an experimental research was carried out. Two pre-cracking levels of damage were analyzed and, for each one, three levels of prestress were tested (0%, 20% and 40%). The obtained results showed that the strengthening of damaged RC slabs with prestressed NSM CFRP laminates results in a significant increase on the load carrying capacity at serviceability limit states. Pre-cracked RC slabs strengthened with prestressed NSM CFRP laminates presented a load carrying capacity almost similar to the corresponding uncracked strengthened slabs. To determine the effective prestress level in CFRP laminates, the variation of strain over the length of the CFRP and over time was experimentally recorded. The prestress transfer length was also evaluated. The experimental results revealed that the transfer length of CFRP laminates was less than 150 mm, and the maximum value of strain loss out of transfer length (around 14%) was measured close to the cracked section of the damaged RC slabs. Significant part of strain loss in CFRP laminates occurred during 24 h after releasing the prestress load.